The Descriptions of Parents with Children Suffering from Cancer during Encountering Emergency Situation: A Qualitative Descriptive Study - Putri, Fitria Mahardika; Nugroho, Kristianto; Victoria, Arlies Zenitha (Babali Nursing Research, 2024)
Introduction: Cancer is a chronic disease caused by abnormal cell growth in the body and can affect all ages, including children. Children with cancer are very vulnerable because they experience growth and development, so they need special attention, especially in emergencies, to avoid death and complications. This study aimed to describe parents' perceptions of having children with cancer when the child is in a crisis. Methods: This research design used a qualitative descriptive approach. This study's population was parents with cancer children with sampling using purposive sampling. Data collection through in-depth interview techniques (in-depth interview) using a recorder, field notes, and interview guidelines. Research data in conversation transcripts were analyzed using Colaizzi's method.Result: Five themes developed, including 1) the participant's understanding of the emergency in pediatric cancer, 2) efforts made by participants in caring for children with cancer, 3) participants' experience in managing and treating children with cancer, 4) challenges in treatment, and 5) participants' expectations in the treatment carried out by their children. The experience obtained by participants is a feeling of fear of worsening the situation and negative thoughts that arise & impact the participants' psychology. In addition, the challenges experienced by participants are the cost of traveling the distance between health facilities and residence. Behind it all, participants hope their children will recover from cancer.Conclusion: There is a lack of understanding of parents regarding emergencies in cancer; behind that, there are efforts made, such as efforts to treat children with cancer, struggles to care for children with cancer, and spiritual aspects.